Are Phase 1 Trials Therapeutic? Risk, Ethics, and Division of Labor. (10th June 2012) - Anderson, James A.; Kimmelman, Jonathan
ABSTRACT Despite their crucial role in the translation of pre‐clinical research into new clinical applications, phase 1 trials involving patients continue to prompt ethical debate. At the heart of the controversy is the question of whether risks of administering experimental drugs are therapeutically justified. We suggest that prior attempts to address this question have been muddled, in part because it cannot be answered adequately without first attending to the way labor is divided in managing risk in clinical trials. In what follows, we approach the question of therapeutic justification for phase 1 trials from the viewpoint of five different stakeholders: the drug regulatory authority, the IRB, the clinical investigator, the referring physician, and the patient. Our analysis shows that the question of therapeutic justification actually raises multiple questions corresponding to the roles and responsibilities of the different stakeholders involved. By attending to these contextual differences, we provide more coherent guidance for the ethical negotiation of risk in phase 1 trials involving patients. We close by discussing the implications of our argument for various perennial controversies in phase 1 trial practice.